2002
DOI: 10.1128/aac.46.7.2238-2243.2002
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir Cream for Treatment of Herpes Simplex Labialis: Results of Two Randomized, Double-Blind, Vehicle-Controlled, Multicenter Clinical Trials

Abstract: Acyclovir cream has been available for the treatment of herpes labialis in numerous countries outside the United States for over a decade. Evidence for its efficacy comes from a few small clinical trials conducted in the 1980s. To examine more comprehensively the efficacy and safety of this formulation, we conducted two independent, identical, parallel, randomized, double-blind, vehicle-controlled, large-scale multicenter clinical trials. Healthy adults with a history of frequent herpes labialis were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 20 publications
3
87
2
1
Order By: Relevance
“…It is presumed, but not proven, that a strong antiviral effect hastens wound resolution by decreasing the extent of keratinocyte destruction, the viral antigen load, and the attendant inflammatory response, which impair reepithelization at the site of infection (1,9,11,22). One-day, two-dose oral valacyclovir constitutes a convenient treatment for herpes labialis in comparison to topical therapies, which typically require frequent applications for multiple days (13,15,19,20,23). While direct comparisons between oral and topical therapy have not been conducted, the available data suggest that oral therapy is more effective.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is presumed, but not proven, that a strong antiviral effect hastens wound resolution by decreasing the extent of keratinocyte destruction, the viral antigen load, and the attendant inflammatory response, which impair reepithelization at the site of infection (1,9,11,22). One-day, two-dose oral valacyclovir constitutes a convenient treatment for herpes labialis in comparison to topical therapies, which typically require frequent applications for multiple days (13,15,19,20,23). While direct comparisons between oral and topical therapy have not been conducted, the available data suggest that oral therapy is more effective.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical studies leading to approval demonstrated that the cream was efficacious in shortening the median healing time of classical cold sore episodes by 0.7 to 1.0 days (13 to 17%) compared to the vehicle controls (13,20). Acyclovir 5% cream (Zovirax cream) is also indicated for cold sores and has been shown in two large, well-controlled clinical trials to shorten the duration of classical cold sore episodes by a similar magnitude to that of penciclovir 1% cream (19). The clinical results reported in the two valacyclovir studies indicate a difference between valacyclovir and placebo-treated patients in mean classical lesion healing time of 1.1 to 1.3 days (18 to 21%) ( Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations